2012
DOI: 10.4067/s0718-58392012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential use of Photo-Selective Nets for Fruit Growth Regulation in Apple

Abstract: The effect of shading (i.e. reduction of sunlight availability) on fruit growth physiology has been widely studied in apple (Malus domestica Borkh.), but little knowledge exist about fruit growth responses to changes in the light spectrum. The aim of the present research was to study the effect of use of colored nets with differential sunlight transmission in the blue (B, 400-500 nm), red (R, 600-700 nm) and far-red (FR, 700-800 nm) spectra on apple fruit growth and physiological associated responses. Three ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 22 publications
7
43
0
2
Order By: Relevance
“…This indicates that although significant differences were observed in the RGR and AGR of the fruit ( Figure 8A and 8B), these had no effect on the final fruit weight at harvest (Table 1). In other fruit trees such as apple and peach it has been determined that the final fruit size is resulting of seasonal AGR and RGR variations during the whole season fruit development (Bastías et al, 2012). In the present study was observed that between 11-20 DAFB the AGR and RGR were significantly greater under high tunnel, which could be in part compensating the partial fruit weight losses measured after 20 DAFB (Figure 8).…”
Section: Yield and Precocitysupporting
confidence: 64%
See 1 more Smart Citation
“…This indicates that although significant differences were observed in the RGR and AGR of the fruit ( Figure 8A and 8B), these had no effect on the final fruit weight at harvest (Table 1). In other fruit trees such as apple and peach it has been determined that the final fruit size is resulting of seasonal AGR and RGR variations during the whole season fruit development (Bastías et al, 2012). In the present study was observed that between 11-20 DAFB the AGR and RGR were significantly greater under high tunnel, which could be in part compensating the partial fruit weight losses measured after 20 DAFB (Figure 8).…”
Section: Yield and Precocitysupporting
confidence: 64%
“…It has been demonstrated that the photosynthetic capacity on citrus trees can improve when PAR decreases, reducing photoinhibition by excess light, which consequently improves the photochemical efficiency of photosystem II (Medina et al, 2002). A decrease in PAR availability can also induce photo-morphogenetic responses associated with the phenomenon known as 'shade avoidance' whose response is regulated by phytochrome activity altering shoot elongation and leaf area with ensuing effects on photo-assimilate partitioning and fruit growth (Bastías et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This should affect not only environmental and soil conditions (Bastías et al, 2012b;Cowan et al, 2014), but also in the photosynthetic apparatus (Lobos et al, 2013). Therefore, the objective of the present study was to evaluate the effect of different radiation intensities on chlorophyll fluorescence variations, fruit quality and productive parameters in blueberry (Vaccinium virgatum Aiton) 'Ochlockonee' plants.…”
Section: Introductionmentioning
confidence: 99%
“…These covers selectively filter direct solar radiation by modifying the amount of radiation passing through them (Bastías et al, 2012b). In addition to this protective function against radiation, this technique could be increasingly needed to mitigate adverse effects of climate change on fruit trees (Demchak, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown how netting can interfere with the sexual activity and flight of CM (Tasin et al 2008;Sauphanor et al 2012;Ioriatti and Tasin 2018). The occurrence of nets in eastern Washington appears to be expanding rapidly due to this effect and to protect fruits from sunburn while enhancing tree physiology (Lloyd et al 2005;Bastias et al 2012). Unfortunately, the use of netting may exacerbate management of other pests such as aphids (Dib et al 2010).…”
Section: Physical Crop Protectionmentioning
confidence: 99%